PELATIHAN KNOWLEDGE MANAGEMENT DAN KEWIRAUSAHAAN PADA MASYARAKAT KECAMATAN SIAK HULU KABUPATEN KAMPAR - Deswarta Deswarta; Masnur Masnur; Hamanda Hadi Saputra; Aisyah Sofia Rj; Radja Bintang Pratama Hsb (CV. Denasya Smart Publisher, 2026)
Siak Hulu District, Kampar Regency has considerable human resource potential and local economic capacity; however, these have not been optimally supported by adequate knowledge management and entrepreneurial skills. This community service activity aims to enhance participants’ understanding and skills in applying knowledge management as a foundation for entrepreneurial development. The program was implemented through interactive lectures, group discussions, case studies, and simple practical activities involving 30 participants consisting of beginner entrepreneurs and productive community members in a one-day training session.The results indicate an improvement in participants’ understanding of knowledge creation, storage, sharing, and utilization, as well as increased motivation and readiness to develop their businesses creatively and innovatively. This activity contributes to fostering an adaptive and competitive entrepreneurial community in Siak Hulu District, Kampar Regency..